Effects of intensive fasting and methyl groups of feed on liver metabolism and welfare in breeding blue fox (Alopex lagopus) vixens - Nenonen, Nita; Nieminen, Petteri; Dahlman, Tuula; Valaja, Jarmo; Pölönen, Ilpo; Anttila, Marjukka; Mustonen, Anne-Mari; Rekilä, Teppo (International Fur Animal Scientific Association (IFASA), 2004)
The feeding trial was carried out on 60 blue fox vixens before the breeding season (age six months at the beginning of the trial). The aim of the present study was to find out to which extent low dietary protein supplemented with methyl donors affects fat and liver metabolism and body weight reduction in the period November-March. Treatments were: control (blue fox feed, 20% protein from ME), Alimet® (control feed with supplemental methionine hydroxy analogue), betaine (control feed with supplemental betaine), choline (control feed with supplemental choline), methionine (control feed with supplemental DL-methionine) and positive control (commercial blue fox feed, 35 % protein from ME). Body weight loss, blood parameters, liver histology, enzyme activities, and cortisol:creatinine ratio of urine were measured. In conclusion, the experiment showed that methyl donors had no effect on health status on blue fox vixens given a low protein diet during the body fat mobilisation period. Generally, the low dietary protein level was reflected in some health parameters, but no animals revealed symptoms of malnutrition. The results demonstrated that the blue fox have extreme abilities to maintain health on a suboptimal diet during body fat mobilisation. v ok